2018
DOI: 10.1155/2018/8014213
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lactate or Lactate Clearance: Which Is Robust to Predict the Neurological Outcomes after Cardiac Arrest? A Systematic Review and Meta-Analysis

Abstract: Aims Lactate and lactate clearance were supposed to be associated with cardiac arrest outcomes, but studies obtained different results. Thus, we conducted this meta-analysis to investigate the association between lactate or lactate clearance and neurological outcomes and their usefulness for prediction of neurological outcomes. Methods We conducted a systematic search in PubMed, Web of science, EMBASE, Medline, and Google Scholar until May 1, 2018, for relevant studies. Studies reporting lactate, lactate clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(64 reference statements)
2
8
0
Order By: Relevance
“…The prognostic value of serum lactate levels was studied in OHCA patients. A previous metaanalysis reviewed 22 articles with 6553 participants and, although the constituent studies were highly heterogeneous, lactate levels at 24, 48, and 72 h from admission were associated with poor neurological outcomes [13]. Like previous studies, our study also showed that all serial serum lactate levels from 0-72 h were associated with neurological outcomes.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The prognostic value of serum lactate levels was studied in OHCA patients. A previous metaanalysis reviewed 22 articles with 6553 participants and, although the constituent studies were highly heterogeneous, lactate levels at 24, 48, and 72 h from admission were associated with poor neurological outcomes [13]. Like previous studies, our study also showed that all serial serum lactate levels from 0-72 h were associated with neurological outcomes.…”
Section: Resultssupporting
confidence: 73%
“…Lactate is produced from anaerobic metabolism after hypoxic tissue injury. During cardiac arrest, the anoxic state leads to lactate accumulation, and the serum lactate level is likely to be a useful marker of brain hypoxia, as also recommended in the Utstein guidelines [13]. Conversely, decreased lactate is a surrogate marker for adequate tissue perfusion after the return of spontaneous circulation (ROSC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Serum lactate level is a good prognostic indicator for tissue perfusion deficit. It has recently been reported that blood lactate level measured on arrival is useful as a prognostic predictor for cardiac arrest in adult and neonates who undergo therapeutic hypothermia (16)(17)(18)(19). Lee et al reported that high serum lactate levels measured within 1 h of ROSC, were positively associated with hospital mortality and poor neurological outcomes in 443 adult OHCA patients treated with therapeutic hypothermia (17).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that high serum lactate levels measured within 1 h of ROSC, were positively associated with hospital mortality and poor neurological outcomes in 443 adult OHCA patients treated with therapeutic hypothermia (17). A systematic review and meta-analysis also showed that high serum lactate levels on admission were associated with poor neurological outcomes after cardiac arrest, whereas the association between serum lactate clearance and neurological outcomes was not so stable (18). In the present study, it was found that an initial lactate level ≤80 mg/dL within 1 h of ROSC was positively associated with a 6-month favorable neurological outcome in pediatric asphyxial OHCA treated with therapeutic hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 236 cases of cardiac arrest by Dell'Anna et al [34] found that the first lactic acid concentration after ROSC was an independent risk factor for patients with poor neurological prognosis at 3 months. Zhou et al [35] conducted a meta-analysis of 23 studies involving a total of 6720 cardiac arrest patients and showed that patients with good neurological prognosis had lower plasma lactate concentrations than those with poor prognosis at admission, 12 h, 24 h, and 48 h after resuscitation. During cardiac arrest and CPR, the anaerobic glycolytic pathway is activated to cause lactic acid accumulation and microcirculation disorders, which further aggravate organ and tissue ischemia and hypoxia, thereby causing organ dysfunction, and leading to poor neurological prognosis.…”
Section: Discussionmentioning
confidence: 99%